Microsurgical Perspective for Uncommon Variations Associated with the Vertebrobasilar Junction: An Anatomical and Radiologic Investigation - Karadağ, Ali; Şenoğlu, Mehmet; Turkis, Ömer Furkan; Kınalı, Burak; Güvençer, Mustafa; Pekçevik, Yeliz; Okromelidze, Lela; Middlebrooks, Erik H.; Çamlar, Mahmut; Tanrıöver, Necmettin (Cerrahpaşa Medical Journal, 2022)
Objective: Anatomic variations of the vertebrobasilar junction have been described as uncommon, but may have important neurosurgical implications. The aim of this study is to emphasize the importance of the variations during the surgery and report the frequency of detected uncommon variations through cadaver dissection and computed tomography angiography. Methods: A combined cadaveric and radiologic study was performed to assess for basilar artery fenestration, intervertebral transversal anastomosis, and persistent primitive lateral vertebrobasilar anastomosis. Thirteen formalin-fixed human cadaveric heads were perfused with red- and blue-colored silicone and dissected in a stepwise manner through an endoscopic endonasal transclival approach. Radiologic data from 887 subjects were retrospectively analyzed for the presence of intervertebral transversal anastomosis. Results: Basilar artery fenestration was found in 7 patients (0.8%), intervertebral transversal anastomosis in 1 (0.1%), and persistent primitive lateral vertebrobasilar anastomosis in 1 (0.1%) by CTA analysis. Conclusion: Anatomic variations of the vertebrobasilar junction are a rare, but important, finding in vascular neurosurgery practice. We also report the first case of intervertebral transversal anastomosis discovered through human brain dissection. Cite this article as: Karadağ A, Şenoğlu M, Turkis ÖF, et al. Microsurgical perspective for uncommon variations associated with the vertebrobasilar junction: An anatomical and radiologic investigation. Cerrahpaşa Med J. 2022;46(2):97-100.